ICoAIMS 2025 gathers experts, strengthens role of mathematics, statistics and data science in digital era - Naqiah, Puaad (UMPSA, 2025)
KUALA LUMPUR, 23 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) once again takes a step forward as a leader in the field of Applied Mathematics and Industrial Statistics with the organisation of the 5th International Conference on Applied & Industrial Mathematics and Statistics 2025 (ICoAIMS 2025), held from 23 to 24 May 2025 at The Pearl Hotel, Kuala Lumpur.